2017
DOI: 10.1155/2017/3754942
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Ferulate Protects against Angiotensin II-Induced Cardiac Hypertrophy in Mice by Regulating the MAPK/ERK and JNK Pathways

Abstract: Background and Objective. It has been reported that sodium ferulate (SF) has hematopoietic function against anemia and immune regulation, inflammatory reaction inhibition, inhibition of tumor cell proliferation, cardiovascular and cerebrovascular protection, and other functions. Thus, this study aimed to investigate the effects of SF on angiotensin II- (AngII-) induced cardiac hypertrophy in mice through the MAPK/ERK and JNK signaling pathways. Methods. Seventy-two male C57BL/6J mice were selected and divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Elevation in ROS generation including superoxide anions, H 2 O 2 , and hydroxyl radicals has known to activate the MAPKs to induce hypertrophic effects and elimination of these ROS by scavengers or antioxidants potentially attenuates cardiac hypertrophy . In our recent study administration of superoxide anion scavenger on rats hearts suppresses hypoxia associated cardiac apoptosis in rats with sleep apnea by elevating IGFI associated survival pathway and by enhancing the phosphorylation of Bad .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Elevation in ROS generation including superoxide anions, H 2 O 2 , and hydroxyl radicals has known to activate the MAPKs to induce hypertrophic effects and elimination of these ROS by scavengers or antioxidants potentially attenuates cardiac hypertrophy . In our recent study administration of superoxide anion scavenger on rats hearts suppresses hypoxia associated cardiac apoptosis in rats with sleep apnea by elevating IGFI associated survival pathway and by enhancing the phosphorylation of Bad .…”
Section: Discussionmentioning
confidence: 85%
“…Various alternative medicines are been evaluated for their potential to establish cardiac protection . Our previous studies and several other reports show that activation of pJNK and p38 MAPKs play an important role in cardiac hypertrophic effects and associated apoptosis . Activation of ERK, JNK and p38 MAPKs stimulates the expression of early proteins of hypertrophy, like the c ‐ Fos and c ‐ Jun and promotes hypertrophy and apoptosis, therefore, the role of MAPKs is involved in the pathogenesis of cardiac hypertrophy …”
Section: Discussionmentioning
confidence: 96%
“…IGF1R is a protein and transmembrane tyrosine protein receptor which is involved in the IGF1/MAPK signalling pathway [48,49]. P38MAPK, an important member of the MAPK signalling pathway, can activate the MAPK signalling pathway [50][51][52][53], causing the proliferation of cells [54][55][56]. Moreover, our previous studies have shown that p38MAPK signalling is inhibited by miR-451 in early DN [15].…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinase (MAPK) is able to promote the proliferation and transmission of stress signals (31). Its family includes extracellular signal-related kinases, c-Jun N-terminal kinases and p38 (32).…”
Section: Discussionmentioning
confidence: 99%